Decompression, an Unusual Treatment Option for Multicystic Ameloblastoma: Concepts and Controversies - Cinthya María Quisiguiña-Salem; Alejandro Alonso-Moctezuma; Carla Monserrat Martínez; Fabiola Salgado-Chavarría; Itzel Legorreta-Villegas; James Jerez-Robalino (Case Reports in Dentistry)
Conclusion: The solid ameloblastoma may have a cystic component, in which there is the possibility of diagnostic errors when studying an incisional biopsy; for this reason, the definitive diagnosis should be established until complete enucleation of the lesion is performed. This characteristic in a solid ameloblastoma makes possible a positive response to decompression, making it easier to perform the enucleation subsequently, avoiding other aggressive treatments that can dramatically affect the patient’s quality of life and also avoiding costly reconstruction bills.